Integrated Employee Performance Monitoring using Dashboard and Predictive Analytics - Jameel, Nurul Afiqah (IRC, 2019)
Employees are well-known to be the most valuable asset in an organization. The employees are the backbone of determining the success of a company. Without employees, an organization would not be able to satisfy their customer. Many organizations will try their best in fulfilling the demand from customer where they will push their employee to always deliver the best. However, there are company who over limit their request which causing the employees to have workloads more than he or she supposed to. Therefore, this project is focusing on the development of Integrated Employee Performance Monitoring using Dashboard and Predictive Analytics. The project consists of web application, database and dashboard. The employees will need to insert the information needed to predict their performance on that particular week. Then, the inputs are going to be stored in the MySQL database. The dashboard is being built by using a data visualization tool called Power BI and it also incorporates Python for extensive visualization which will portray the graphs for each employee’s performances. Last but not least, Microsoft Azure will be used to store all the back end codes. It is a cloud computing service created by Microsoft for building, testing, deploying, and managing applications and services through Microsoft-managed data centres. This project is expected to help the superiors in the company to monitor their employee’s performance from time to time. Based on the predictions, the employer are able to provide tasks based on their employee’s ability in order to avoid the employee from overwork or overstressed that could lead to inefficiency in delivering the given task. The prediction made will also allow the employer to know which employee have excellence working performance. Moreover, it is the dream of human resources (HR) practitioners for employees to achieve people excellence in the workplace.